Implementation of Management Strategies for Diabetes and Hypertension: from Local to Global Health in Cardiovascular Diseases - Bloomfield, Gerald S. (Glob Heart, 2015)
Diabetes and hypertension are chronic conditions that are growing in prevalence as major causal factors for cardiovascular disease. The need for chronic illness surveillance, population risk management, and successful treatment interventions are critical to reduce the burden of future cardiovascular disease. In order to address these problems, it will require population risk stratification, task sharing and shifting, and community- as well as network -based care. Information technology tools also provide new opportunities for identifying those at risk and for implementing comprehensive approaches to achieving the goal of improved health locally, regionally, nationally and globally. This article discusses ongoing efforts at one university health center in the implementation of management strategies for diabetes and hypertension at the local, regional, national, and global levels.